Factors Affecting Young Shoppers’ Online Shopping Preference in Kelantan, Malaysia - Nazaria, Md. Aris; Ruziah, A. Latif; Nurnais Safiy, Zainal; Khalisah Khairina, Razman; Razman, Anuar (Human Resource Management Academic Research Society, 2021)
The growth of online shopping is impressive. The presence of social media platforms accelerates the way companies connect directly with consumers. In other words, consumers use internet as shopping channel instead of physically walk into the traditional brick-and-mortar retail stores. Nowadays, majority of the young people are associated with technologies and digital media. Online shopping has become a significant part of their lifestyle. The objective of this study concerns to understand the demography and perceptions towards online shopping orientation of young Malaysian in Kelantan. Therefore, a sample of 101 young shoppers in Kota Bharu, Kelantan were asked for input and descriptive analysis was done to examine factors shaping their online shopping preference. Based on the result, the study highlighted three significant findings. Perceived ease of use, perceived usefulness and past online shopping experience are the key factors which influence online shopping orientation for young shoppers. Consequently, the finding is important for business developers to form their e-marketing strategies in creating a highly convenient e-store platform to fit the changing needs of young shoppers’ lifestyles towards online shopping experience especially in Kelantan.